The Diagnostic Utility of Growth Ultrasound for the Indication of Maternal Overweight or Obesity - Sakowicz, Allie; Grobman, William A.; Miller, Emily S. (American Journal of Perinatology, 2022)
Objective The objective of this study was to evaluate the diagnostic utility of serial growth ultrasounds for the indication of maternal overweight or obesity.Study Design This is a retrospective cohort study of all women with a body mass index ≥25 kg/m2 who underwent at least one growth ultrasound at ≥24 weeks gestation and delivered at a single tertiary care institution between January 2010 and December 2013. Women were excluded if they had other medical indications for growth ultrasounds. Ultrasounds were divided into three gestational age epochs: 24 to 316/7 weeks, 32 to 356/7 weeks, and ≥36 weeks. Outcomes examined included the accuracy of sonographic detection of fetal growth restriction (FGR) and fetal overgrowth compared with diagnoses of small for gestational age (SGA) and large for gestational age (LGA) based on the birth weight. The test characteristics of ultrasound and the number needed to screen (NNS) to detect growth abnormalities at the time of birth were estimated for each condition and gestational age epoch. The NNS for the detection of fluid abnormalities was also assessed.Results During the study period, 3,945 eligible sonograms were performed in 2,928 women. FGR was identified on ultrasound in 42 (1.4%) women, fetal overgrowth in 94 (3.2%) women, oligohydramnios in 35 (1.2%) women, and hydramnios in 41 (1.4%) women. The NNS for the diagnoses of SGA, LGA, oligohydramnios, and hydramnios at delivery was at least 137 prior to 32 weeks of gestation and decreased (i.e., at least 45 and 16, for 32 to 356/7 weeks and ≥36 weeks, respectively) with advancing gestational age epochs.Conclusion If growth ultrasounds are to be performed for the sole indication of maternal overweight or obesity, consideration should be given to delaying initiation until at least 32 weeks of gestation given the infrequency of growth and fluid abnormalities identified earlier.Key Points
Keywords: Obesity; oligohydramnios; hydramnios; small for gestational age; large for gestational age; fetal growth restriction